ETNOGRAFI PÅ AFVEJE: Om anvendeligheden af begrebet „lokal viden" i aids-forebyggelse - Godtfredsen, Ulla (Tidsskriftet Antropologi, 1996)
Ulla Godtfredsen: Ethnography Gone Astray. On the Applicability of “Local Knowledge” in HIV/AIDS Prevention Researchers and organisations working in the field of AIDS have increasingly sought to explore and consider „local knowledge" as a means of adapting AIDS prevention programmes to local cultural settings. This has been done in order to translate “Western scientific facts” on AIDS into locally intelligible terms in the belief that appropriate information would make target groups alter their behaviour, sexual and otherwise, accordingly. By going through ethnographic material on traditional healing and female circumcision in Guinea-Bissau, the author shows how „ocal knowledge” cannot be conceived as a fixed and bounded category. Knowledge is intertwined with practice and continually changed in interaction with new forms of knowledge. Also, the description of „local" knowledge entails the demarcation of fixed local entities which do not correspond with the pluralism of any social setting. It is therefore difficult, if not impossible, to map out one form of „local knowledge" and replace that with another and “betler” set of (scientific) knowledge. Efforts against HIV/AIDS must be part of a broader cultural development process.